Untargeted profiling of urinary steroid metabolites after testosterone ingestion: opening new perspectives for antidoping testing. (October 2014) - Boccard, Julien; Badoud, Flavia; Jan, Nicolas; Nicoli, Raul; Schweizer, Carine; Pralong, François; Veuthey, Jean-Luc; Baume, Norbert; Rudaz, Serge; Saugy, Martial
Aim: Antidoping procedures are expected to greatly benefit from untargeted metabolomic approaches through the discovery of new biomarkers of prohibited substances abuse.Results: Endogenous steroid metabolites were monitored in urine samples from a controlled elimination study of testosterone undecanoate after ingestion. A platform coupling ultra-high pressure LC with high-resolution quadrupole TOF MS was used and high between-subject metabolic variability was successfully handled using a multiblock data analysis strategy. Links between specific subsets of metabolites and influential genetic polymorphisms of the UGT2B17 enzyme were highlighted.Conclusion: This exploratory metabolomic strategy constitutes a first step toward a better understanding of the underlying patterns driving the high interindividual variability of steroid metabolism. Promising biomarkers were selected for further targeted study.